A conformação dos grupos de pesquisa em biotecnologia da cana de açúcar na região norte-fluminense: a perspectiva do "novo sistemismo" - Adelia Maria Miglievich Ribeiro; Fabricio Monteiro Neves (Ciências Sociais Unisinos)
Through the Theory of the Social Systems of the German sociologist Niklas Luhmann, we argue about the scientific, technological, economic, legal and political standing subsystems in the generation of the biotechnology of sugarcane in the North of Rio de Janeiro state, Brazil. We give particular emphasis to Campos dos Goytacazes, where the groups of research are settled, hosted at Universidade Estadual do Norte Fluminense (UENF) and at Universidade Federal Rural do Rio De Janeiro (UFRRJ). In the case hereof, we verify the processes of interaction between functional differentiated daily systems of the scientific practice through the analyses of projects and documents and based on interviews. We also confirm the distinct forms of assimilation and reaction to the information of the environment by the structure of expectation of the groups. As a result, we emphasize how much local production of modern biotechnology needs oriented public policies to carry it out. We confirm, thus, the tendency that the process of generation of technology in peripheral countries works due to a structural coupling between State, science and economy, whereas, in the main countries, this process is made independently of the main performance of the first one.